2021
DOI: 10.3389/fpsyt.2021.629428
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and Psychological Distress in Male and Female Anabolic-Androgenic Steroid Users: A Multigroup Latent Class Analysis

Abstract: The relationship between anabolic-androgenic steroid (AAS) use and aggression and psychological distress requires further elucidation. No previous study has examined whether the latent patterns of aggression and psychological distress are the same in male and female AAS users. Multigroup latent class analysis (MLCA) can be used to classify individuals into groups based on their responses on a set of variables, and to investigate measurement invariance across subgroups. We therefore conducted a MLCA to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 63 publications
2
24
1
1
Order By: Relevance
“…This study observed a high prevalence of psychiatric effects among AAS users, which were not associated with the doses of AAS taken by the participants and negatively associated with their time of AAS use. Instead of contradicting the evidence of a dose‐related association between the use of AAS and aggression seen in randomly controlled trials – as summarized by Chegeni et al 8 —we believe that these results highlight the complexity of ecological observations of AAS use. A large body of literature indicates that factors other than the sheer exposure to AAS can influence the onset and severity of adverse effects, such as individual vulnerabilities, distinct effects of different AAS and strategies adopted by AAS users to treat and prevent adverse effects 5,53–57 .…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…This study observed a high prevalence of psychiatric effects among AAS users, which were not associated with the doses of AAS taken by the participants and negatively associated with their time of AAS use. Instead of contradicting the evidence of a dose‐related association between the use of AAS and aggression seen in randomly controlled trials – as summarized by Chegeni et al 8 —we believe that these results highlight the complexity of ecological observations of AAS use. A large body of literature indicates that factors other than the sheer exposure to AAS can influence the onset and severity of adverse effects, such as individual vulnerabilities, distinct effects of different AAS and strategies adopted by AAS users to treat and prevent adverse effects 5,53–57 .…”
Section: Discussioncontrasting
confidence: 65%
“…Investigations of the psychiatric effects of androgenic‐anabolic steroids (AAS) have been conducted since the use of exogenous testosterone in the treatment of depression and melancholia was observed in the 1940s 1 . Current evidence corroborates that the use of AAS can have beneficial effects on the central nervous system (CNS) such as reduction of depressive symptoms in men, 2,3 as well as detrimental psychiatric outcomes such as increased aggressiveness and anxiety 4–9 . Possible mechanisms that explain central effects of AAS include binding to and modulating the expression of CNS androgenic receptors, 10,11 and interfering with biosynthesis of endogenous neurosteroids 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was interesting to note, however, the relatively greater use by females of “other anabolic agents.” AAS induce abnormal endogenous hormone secretion, producing such reversible or irreversible damage as acne vulgaris, androgenic alopecia, hypertrichosis, liver cancer, cardiovascular risks, renal failure, and increased tendon ruptures (Hartgens and Kuipers, 2004 ). AAS are also known to induce psycho-behavioral disorders leading to violence or depression, with more aggressive responses in men (Gruber and Pope, 2000 ; Chegeni et al, 2021 ). AAS also induce gender-specific side effects, with either gynecomastia, testicular atrophy, azoospermia, and infertility in men or amenorrhea, uterine atrophy, and clitoral enlargement in women (Liu and Wu, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent steps these assumptions are relaxed (parameters are freed). We employ the forward inclusion of differences strategy (Chegeni et al, 2021;Hagenaars, 1990;Kankaras et al, 2010). Before introducing the group variable, a model is estimated irrespective of the grouping variable (complete homogeneity; cf.…”
Section: B) Testing For Equivalence Of Measurement Invariancementioning
confidence: 99%